2001
DOI: 10.1021/ic0104297
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of an Al693- Cluster with 51 Naked Al Atoms:  Analogies and Differences to the Previously Characterized Al772- Cluster

Abstract: A disproportionation process of a metastable AlCl solution with a simultaneous ligand exchange-Cl is substituted by N(SiMe(3))(2)-leads to a [Al(69)[N(SiMe(3))(2)](18)](3-) cluster compound that can be regarded as an intermediate on the way to bulk metal formation. The cluster was characterized by an X-ray crystal structural analysis. Regarding its structure and the packing within the crystal, this metalloid cluster with 4 times more Al atoms than ligands is compared to the [Al(77)N(SiMe(3))(2)](20)](2-) clust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0
7

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(53 citation statements)
references
References 33 publications
2
44
0
7
Order By: Relevance
“…To prepare a large amount of the cluster compound containing the [Ga 64 (GaR) 20 ] 4À unit (R = N(SiMe 3 ) 2 ), [6] which exhibits unexpected conductivity behavior (superconductivity below 7 K and metallic conductivity above 7 K), [7,8] we applied a new technique for the synthesis of the metastable GaBr solution which is the essential starting material for most of the metalloid Ga cluster compounds. [5] This new technique has been applied recently for the preparation of metastable GeBr.…”
Section: Resultsmentioning
confidence: 99%
“…To prepare a large amount of the cluster compound containing the [Ga 64 (GaR) 20 ] 4À unit (R = N(SiMe 3 ) 2 ), [6] which exhibits unexpected conductivity behavior (superconductivity below 7 K and metallic conductivity above 7 K), [7,8] we applied a new technique for the synthesis of the metastable GaBr solution which is the essential starting material for most of the metalloid Ga cluster compounds. [5] This new technique has been applied recently for the preparation of metastable GeBr.…”
Section: Resultsmentioning
confidence: 99%
“…The synthesis of [Al 57 {AlN(SiH 3 ) 2 } 20 ] 2− by Köhnlein et al (2001) was a breakthrough in the chemistry of ligand-stabilized metal clusters, in general, and of aluminium, in particular. A consideration of the structural features of the aluminium core and the relevant literature revealed that there was no systematic study of Al n clusters in the range up to 60 atoms, which motivated the first systematic theoretical study of clusters of Al in the range up to 150 atoms (Ahlrichs & Elliott 1999).…”
Section: Clusters Of Aluminiummentioning
confidence: 99%
“…[2, 3,6] Anders als in vielen metalloiden Aluminiumclustern, [7] deren Al-Atome bereits Bindungsmotive der fcc-Packung des Metalls zeigen, findet sich in 1 das Al 8 Al 30 (AlCp*) 12 -Strukturmotiv (siehe Hintergrundinformationen). Um diese noch nicht verstandene Strukturbeeinflussung durch die Liganden zu untersuchen, wandten wir uns einem modifizierten Amid-Liganden zu, bei dem eine der SiMe 3 -Gruppen des von uns früher verwendeten N(SiMe 3 ) 2 -Restes durch den sperrigen Dipp-Rest (Dipp = 2,6-iPr 2 C 6 H 3 ) ersetzt ist.…”
Section: Professor Heinrich Nöth Zum 80 Geburtstag Gewidmetunclassified
“…Um diese noch nicht verstandene Strukturbeeinflussung durch die Liganden zu untersuchen, wandten wir uns einem modifizierten Amid-Liganden zu, bei dem eine der SiMe 3 -Gruppen des von uns früher verwendeten N(SiMe 3 ) 2 -Restes durch den sperrigen Dipp-Rest (Dipp = 2,6-iPr 2 C 6 H 3 ) ersetzt ist. In Analogie zum Sn 15 R' 6 -Cluster 2 mit R' = N(Dipp)SiMe 3 [8] und dem Si-zentrierten metalloiden AlCluster Si@Al 14 Cp* 6 (3) [9] (Abbildung 1) konnten wir den Cluster Si@Al 14 R' 6 synthetisieren [10] und in orientierenden Untersuchungen wenige Kristalle eines Al 48 R' 12 -Clusters erhalten. [11,12] Zur Optimierung der Synthese dieses Clusters und zur Herstellung weiterer Si-haltiger Cluster [13] variierten wir die Reaktionsbedingungen drastisch und erhielten dabei den Si@Al 56 R' 12 -Cluster 5, in dem ein SiAl 44 Kristalle von 5 und 5 a sind in den üblichen Lösungsmit-teln nicht löslich, sodass kein NMR-Spektrum in Lösung aufgenommen werden konnte.…”
Section: Professor Heinrich Nöth Zum 80 Geburtstag Gewidmetunclassified
See 1 more Smart Citation